2002
DOI: 10.1055/s-2002-32731
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Criteria for the Diagnosis of Allied Diseases of Hirschsprung's Disease in Adults

Abstract: A few reports in the literature have discussed the histologic criteria for the diagnosis of allied diseases of Hirschsprung's disease in adults, and studies report that intestinal neuronal dysplasia (IND) in adults may develop from IND in infants. The aim of this study was to examine the differences between the histological findings of IND in infants and those in adults, and to assess whether allied diseases of Hirschsprung's disease (HD) in adults should be considered as congenital or acquired diseases. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
1
10
0
1
Order By: Relevance
“…Recent studies from Japan show an increased incidence of complicated right-sided diverticulitis, so that the dimension of resection needs to be discussed again [12]. Our own experiences in surgical therapy for right-sided diverticulitis are also supported by other authors [1,2,4,16,23].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Recent studies from Japan show an increased incidence of complicated right-sided diverticulitis, so that the dimension of resection needs to be discussed again [12]. Our own experiences in surgical therapy for right-sided diverticulitis are also supported by other authors [1,2,4,16,23].…”
Section: Discussionsupporting
confidence: 68%
“…The clinical picture of IND contains signs of intestinal obstruction of the low type. With the description of cases of IND in adult patients, the onset of IND symptoms has expanded from the first year of life to adulthood [16]. An isolated form of IND was described in nearly 60% of adult patients suffering from chronic constipation, and it is supposed that these patients may develop inflammatory bowel disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hypoganglionosis is usually defined by presence of small, sparse, myenteric ganglion cells compared with controls [19,20]. Diagnosis by this criterion might depend on subjective insight by pathologists because of lack of objective criteria.…”
Section: Discussionmentioning
confidence: 99%
“…This last finding, characteristic of Hirschsprung's disease, is rarely discussed in intestinal neuronal dysplasia type B and can be considered as one of the criteria for its diagnosis. 8,14,36,[40][41][42][43] When comparing different age groups, based on the cutoff age of 1 year, no statistically significant differences were observed in the qualitative analysis of the morphological changes verified in the (Table 2). Despite evidence that the histopathological changes suggestive of immaturity could change with age, through maturation and apoptosis, 21,36,[44][45][46] our results showed that these changes were present in both age groups and call into question the need to establish an age cutoff for the diagnosis of intestinal neuronal dysplasia type B.…”
Section: Discussionmentioning
confidence: 99%